The Influence Of Sharia Economic Education On The Financial Awareness And Attitudes Of The Young Generation - Khalid, Nour; Cunayah, Cucun; Firmansyah, Alvin (Doktoral Ilmu Manajemen, Universitas Pasundan, 2024)
This research aims to analyze the influence of sharia economic education on the financial awareness and attitudes of the younger generation. Sharia economics education is considered important in forming a good understanding of financial principles in accordance with Islamic teachings. This research uses quantitative methods with a survey approach, involving 300 respondents from school and college students who have received sharia economics education. Data were analyzed using multiple linear regression to test the relationship between sharia economic education variables and financial awareness and attitudes. The research results show that sharia economic education has a positive and significant influence on the financial awareness of the younger generation. The younger generation who receive sharia economic education shows a better understanding of personal financial management, the importance of saving, and avoiding the practice of usury. In addition, their financial attitudes are also more likely to support sharia economic principles, such as investing in halal financial instruments and participating in philanthropic activities. The implications of this research show the importance of integrating sharia economic education in the formal education curriculum to form good financial awareness and attitudes among the younger generation. It is hoped that this education can create a generation that is not only financially intelligent, but also has high moral integrity in accordance with Islamic values.